EMERGY; DEFINISI DAN APLIKASINYA DALAM MENDUKUNG PENGAMBILAN KEPUTUSAN UNTUK KEGIATAN KONSERVASI - Puji Rahmadi; Lee Suk-Mo (Jurnal Harpodon Borneo, 2012)
This paper was addressed to introducing new method of measuring the real wealth of environmental value either in the ecological point of view or economically. The new method proposed here was “Emergy analysis” (the available energy of one kind previously used up directly and indirectly to make a production or service). The Emergy analysis was used to gain overviews of the relationship between economy and ecology in relation to the decision making whether the environmental need conservations or not. In this paper some Emergy terminology was introduced as well as the definition of Emergy itself. Some of the Emergy terminology introduced here were; Energy, emergy, solar transformity, exergy, empower and EmValue. Procedure to do Emergy analysis was clearly discussed here and followed by Emergy indices calculation. Based on the result of Emergy indices calculations, we will get recommendation to make the suitable decision about a system, environmental or even production activity. Keywords : Emergy, transformity, Emergy-index, conservation.